Characterization of Galena and Vein Paragenesis in the Penjom Gold Mine, Malaysia: Trace Elements, Lead Isotope Study and Relationship to Gold Mineralization Episodes - Zakaria, E.; Fatt, N.T.; Abdul Aziz, J.H.; Sebastien, M.; Charles, M. (Wiley-Blackwell Publishing Asia, 2015)
The Penjom Gold Mine is located 30 km from the Bentong-Raub Suture at the western boundary of the Central Belt in Peninsular Malaysia. Gold mineralization hosted within the vein system is associated with pyrite, arsenopyrite, and minor base metals including galena. Trace element and lead isotope analysis was undertaken on nine samples that represent two stages of galena formed during two tectonic events. Both the Pb isotopes and the trace elements show that the first stage galena within the mineralized areas at the footwall has different geochemical characteristics compared with galena in non mineralized areas in the hanging wall, suggesting that galena crystallized from two different ore fluids and probably at two different times. Higher Te, Se and Bi in the galena from the mineralized area may indicate hydrothermal fluids that migrate through the structural conduit and leached out the metal along the pathway that consist of dominant carbonaceous unit. The Pb isotopic ratio composition are transitional between the bulk crustal growth and an upper crustal growth curve, indicating that derivation was from arc rocks associated with continental crust or a crustal source that includes arc volcanic and old continental sedimentary rocks.